The Jellybeans and the big dance - Numeroff, Laura Joffe (Abrams Books for Young Readers, 2008)
When four young girls meet in dance class, it takes time for them to find a way--and a reason--to pull together as one, but Emily helps them realize that, just like a bag of jellybeans, they can be different and still go well together.